Impact of implant abutment materials on force damping response and marginal fit of implant supported restoration - Amr Mohammed Hussein Elmesery; Amany Mohammed Korsel; Waleed Elshahawy (BMC Oral Health)
Abstract Background The marginal fit and force-damping response of implant-supported restorations play critical roles in the long-term success of dental implants. This study evaluates the effect of implant abutment materials— resin-ceramic material, lithium disilicate, PEEK, and Titanium- on implant-supported restorations' marginal fit and force-damping response. The study offers novel insights into stress distribution and marginal gaps, aiming to optimize implant-supported restoration outcomes. Methods Forty implant abutments were divided into four equal groups: Shofu HC, Tessera, BioHPP, and Titanium. Vertical marginal gap measurements were taken using a digital microscope before and after Cementation, and force damping was assessed using a custom impact test machine. Non-metal abutments were custom-fabricated using STL files and a CAD/CAM machine (CEREC MC X5, Dentsply Sirona) for Tessera (MT/LT-BL2), Shofu HC Block (A3-LT/M), a resin hybrid ceramic (61% zirconium silicate, 39% nano-filler composite), and BioHPP (bredent GmbH & Co KG). Quantitative data were expressed as mean ± SD and analyzed using ANOVA with post hoc Tukey test. Normality was confirmed with the Shapiro–Wilk test, and differences between groups were assessed with an unpaired Student's t-test. Results Before Cementation, the Biohpp group demonstrated the highest marginal gap (35.49 ± 2.31 µm), followed by Titanium (31.05 ± 1.87 µm) and Shofu HC Block (29.35 ± 1.72 µm). Tessera exhibited the lowest marginal gap (23.70 ± 2.99 µm) (P < 0.001). After Cementation, marginal gaps increased across all groups, with Biohpp (46.47 ± 3.10 µm) and Titanium (38.43 ± 2.25 µm) showing the most significant gaps, while Tessera continued to demonstrate the lowest (30.80 ± 1.64 µm) (P < 0.001). In force damping tests, Shofu HC Block recorded the lowest impact force (0.804 ± 0.034 N), followed by Biohpp (0.866 ± 0.027 N) and Tessera (0.920 ± 0.029 N). Titanium exhibited the highest force (0.970 ± 0.033 N), with all results showing statistical significance (P < 0.001). Conclusions Lithium disilicate exhibited the smallest marginal gap before and after Cementation, while PEEK showed the largest, followed by Titanium and resin-ceramic material. Resin-ceramic material had the highest shock absorption for force damping, followed by PEEK and Lithium disilicate, while Titanium recorded the highest impact force, indicating the least damping ability.